Early Childhood Teachers Emotional Labor in Indonesia: A Phenomenological Study - Mukhlis, Akhmad (Universitas Islam Negeri Raden Intan Lampung, 2025)
Managing emotions and displaying positive expressions in unpleasant situations is an inherent aspect of early childhood education (ECE) teaching. This study explores the emotional labor of early childhood teachers in Indonesia, focusing on their perceptions, lived experiences, and the strategies they employ. A qualitative research design with a phenomenological approach was adopted to capture the subjective meanings behind teachers’ emotional experiences. A qualitative approach with a phenomenological method was employed, as it enables an in-depth exploration of teachers’ subjective experiences within their socio-cultural context. Ten teachers from four provinces in Indonesia (East Java, Yogyakarta, West Nusa Tenggara, and Gorontalo) were purposively selected based on a minimum of two years of teaching experience. Data were collected through structured in-depth interviews and validated using member checking and peer debriefing. The analysis followed Moustakas’ six-step phenomenological analysis, guided by Hochschild’s emotional labor theory and Grandey’s extended framework. The findings indicate that emotional labor is an inherent part of the ECE teaching profession, with strategies ranging from surface acting, deep acting, to natural acting. Experienced teachers tend to display positive emotions more naturally, while novice teachers rely more on surface acting. Work experience, personal interest, and educational background contribute to teachers’ emotional management effectiveness. These findings highlight the need for emotional labor training in ECE teacher education curricula and institutional support to promote teachers’ emotional well-being.